A parentalidade invertida em famílias com idosos à luz das lealdades invisíveis - Costa, Christina Mello Amorim (2017)
This dissertation was elaborated with the intention of knowing lived experiences of the relatives along the elderly people, in relation to the dismissed care to them, in a intergenerational perspective, emphasizing the concept of invisible loyalties. The dissertation was executed from the systematic review of literature about the family and elderly people; we conducted a brief history of family in Brazil, including the legal questions. We treat the unfairness and violence suffered by the elderly in brazilian society, as well as the contributions of the family vital cycle theory, emphasizing the last phase, from a reflection about experiences of people with more than eighty years old. We discussed about the situation of family and professional caregivers, how they behave and their impacts inside the family nucleus. Inside the family psychological parameter, the invisible loyalties present a dynamic interaction among the elements which compose a family, through generations that, in coexistence, confers an adherence to the relation system. We count with the participation of four families, which their experiences enriched the comprehension and elucidation of the treatment given to the old people through one construction of genograms and interviews, that shows us the quality of the relationship between sons and elderly parents are the consequences of a whole history of past generations